2016
DOI: 10.5230/jgc.2016.16.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Pylorus-Preserving Gastrectomy for Gastric Cancer

Abstract: Pylorus-preserving gastrectomy (PPG) is a function-preserving surgery for the treatment of early gastric cancer (EGC), aiming to decrease the complication rate and improve postoperative quality of life. According to the Japanese gastric cancer treatment guidelines, PPG can be performed for cT1N0M0 gastric cancer located in the middle-third of the stomach, at least 4.0 cm away from the pylorus. Although the length of the antral cuff gradually increased, from 1.5 cm during the initial use of the procedure to 3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 54 publications
2
59
0
1
Order By: Relevance
“…For early gastric cancer, surgeons started to consider functional preserving gastrectomy to improve the functional outcome and quality of life (QOL) without compromising oncological safety [5][6][7][8][9][10]. Pylorus-preserving gastrectomy (PPG) is such kind of function-preserving surgery, which has gained popularity in East Asian countries [5,[11][12][13]. PPG has become an optional method in Japanese Gastric Cancer Treatment Guideline for tumor located in the middle third portion of the stomach [14].…”
Section: Introductionmentioning
confidence: 99%
“…For early gastric cancer, surgeons started to consider functional preserving gastrectomy to improve the functional outcome and quality of life (QOL) without compromising oncological safety [5][6][7][8][9][10]. Pylorus-preserving gastrectomy (PPG) is such kind of function-preserving surgery, which has gained popularity in East Asian countries [5,[11][12][13]. PPG has become an optional method in Japanese Gastric Cancer Treatment Guideline for tumor located in the middle third portion of the stomach [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that PHCV are necessary for pyloric sphincter functioning in patients after PPG [11] [12]. In recent years the vagal nerves, including hepatic and pyloric branches, have been preserved to prevent PGD including PAF and endoscopic GSRS [13]. Nakabayashi et al [6] suggested that gastric stasis during the early postoperative period in patients after PPG without preservation of the pyloric branch of the vagal nerve is due to tonic and phasic contractions of the pylorus.…”
Section: Discussionmentioning
confidence: 99%
“…According to this data, the size of LAC may be related to the delayed gastric emptying of a diet. Although the LAC gradually increased, from 1.5 cm during the initial use of the procedure to 3.0 cm or more currently, its optimal length still remain unclear [13] [17]. As for the interviews in this study, PAF was observed at a rate of 100% in patients with a short LAC (1.5 to 2.5 cm) and at 7.7% in those with a long LAC (2.6 to 3.5 cm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations